Using chronoamperometry to rapidly measure and quantitatively analyse rate-performance in battery electrodes - Coleman, Jonathan; Nicolosi, Valeria (My University, 2020)
For battery electrodes, measured capacity decays as charge/discharge current is increased. Such rate-performance is usually characterised via galvanostatic charge-discharge measurements, experiments which are very slow, limiting the speed at which rate experiments can be completed. This is particularly limiting during mechanistic studies where many rate measurements are needed. Building on work by Heubner at al., we demonstrate chronoamperometry (CA) as a fast method for measuring capacity-rate curves with hundreds of data points down to C-rates below 0.01C. While Heubner et al. reported equations to convert current transients to capacity vs. C-rate curves, we modify these equations to give capacity as a function of charge/discharge rate, R. We use these expressions to obtain simple equations which can accurately fit data for both capacity vs. C-rate and capacity vs. R at normal rates. Interestingly, at high-rates, the curves obtained from CA deviate from the normal behaviour showing a new, previously unobserved, decay feature. We associate this feature with the very early part of the current transient where electronic motion dominates the current. Using a simple model, we show that the dependence of the high-rate time constant on electrode thickness can be linked to electrode conductivity.
PUBLISHED
cited By 0
Keywords: Rate-performance; Accelerated testing; Fitting-equation